Social Comparison as a Predictor of Shame Proneness Dimensions - Noerhardiyanty, Yessy; Abraham, Juneman (ASPENSI in Bandung, Indonesia, 2015)
ABSTRACT: This study aimed to examine the role of social comparison in predicting two dimensions of a moral emotion, i.e. shame, among employees working in the private companies in the Greatcity of Jakarta, the capital of Indonesia. The participants were 203 employees (99 males, 104 females, age average 28.75 years old, and standard deviation of the age 5.917 years), taken using purposive sampling technique. The measurement scales of this study were adapted and developed from Social Comparison Scale and Shame Proneness Scale. As many as 60 individuals participated in the measurement instrumentâs validity and reliability testing phase. Research design of this study is predictive correlational with simple linear regression as the statistical technique of data analysis. This study found that social comparison can predict Negative Self-Evaluation and Withdrawal Action Tendency, as the dimensions of shame, in negative ways. There are at least two theoretical contributions of this research to the literature of psychology of corruption. First, self-evaluation as a result of the general social comparison, which initially has no moral weight, can have serious implications on oneâs morality, especially through the negative self-evaluation dimension of shame moral emotion. Second, this study provides scientific support to the everyday wisdom suggesting that we should not compare ourselves with others so as not to fall into immorality tendencies, including corruption.KEY WORD: Emotion, moral, shame, comparison, social, employees working, Jakarta city, self-evaluation, predict, and psychology of corruption.Â RESUME: âPerbandingan Sosial sebagai Prediktor Dimensi-dimensi Kecenderungan Rasa Maluâ. Penelitian ini bertujuan untuk menguji peran perbandingan sosial dalam memprediksikan dua dimensi dari sebuah emosi moral, yakni rasa malu, pada pegawai swasta di DKI (Daerah Khusus Ibukota) Jakarta, ibukota Indonesia. Partisipan penelitian ini adalah 203 orang karyawan swasta (99 laki-laki, 104 perempuan, rata-rata usia 28.75 tahun, dan simpangan baku usia 5.917 tahun), diambil dengan teknik penyampelan purposif. Alat ukur penelitian ini diadaptasi dan dikembangkan dari Skala Perbandingan Sosial dan Skala Kerentanan/Kecenderungan Rasa Malu. Sebanyak 60 individu berpartisipasi dalam fase uji validitas dan reliabilitas alat ukur. Desain penelitian ini adalah korelasional prediktif dengan teknik analisis data berupa regresi linear sederhana. Hasil penelitian ini menunjukan bahwa perbandingan sosial mampu memprediksi Evaluasi Diri Negatif dan Tendensi Mengundurkan/Menarik Diri, sebagai dimensi-dimensi rasa malu, dalam arah negatif. Terdapat sedikitnya dua kontribusi teoritis dari penelitian ini terhadap literatur psikologi korupsi. Pertama, penilaian diri sebagai hasil perbandingan seseorang dengan orang lain, yang aslinya tidak memiliki bobot moral, dapat memiliki implikasi serius terhadap moralitas seseorang, khususnya pada dimensi evaluasi diri negatif dari rasa malu. Kedua, penelitian ini memberikan dukungan ilmiah terhadap kebijaksanaan hidup sehari-hari yang meminta agar kita tidak membanding-bandingkan diri dengan orang lain supaya tidak jatuh dalam kecenderungan imoralitas, termasuk berbuat korupsi.KATA KUNCI: Emosi, moral, malu, perbandingan, sosial, pegawai, kota Jakarta, penilaian diri, memprediksi, dan psikologi korupsi.Â Â About the Authors: Yessy Noerhardiyanty, S.Psi. is an Alumna of Psychology Department, Faculty of Humanities BINUS (Bina Nusantara University) in Jakarta; and Juneman Abraham, M.Si. is the Faculty Member-Subject Content Coordinator (FM-SCC) of Community Psychology Studies at the Bina Nusantara University, BINUS Kampus Kijang, Jalan Kemanggisan Ilir III No.45, Palmerah, Jakarta 11480, Indonesia. For academic purposes, the author can be contacted via e-mail at: juneman@binus.ac.idHow to cite this article? Noerhardiyanty, Yessy & Juneman Abraham. (2015). âSocial Comparison as a Predictor of Shame Proneness Dimensionsâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.8(2) November, pp.231-240. Bandung, Indonesia: Minda Masagi Press and UNIPA Surabaya, ISSN 1979-0112. Chronicle of the article: Accepted (July 3, 2015); Revised (September 19, 2015); and Published (November 30, 2015).